Potensi Penggunaan Kayu Hutan Tanaman Rakyat sebagai Elemen Struktur (Sebuah Upaya Perlindungan terhadap Hutan Alami) - Setiyaningsih, Sri Indah; Yeni, Manovri (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
In Indonesia, there are approximately 4,000 types of trees. The demand for wood continues to increase with the development of infrastructure across the country. However, the fact remains that the rapid rate of forest destruction in Indonesia has led to a raw material crisis in the forestry industry. According to SKEPHI (Indonesian Forest Conservation Cooperation Secretariat), regarding the condition of Indonesia's forests during 2007-2008, the manifestation of forest destruction is evidenced by Indonesia breaking the Guinness World Record in 2007 as the fastest forest-destroying country. Another issue faced is the growing population of Indonesia, which results in a large shortage of wood supply and its consequences. Aesthetically, wood is appealing due to its artistic value. Mechanically, wood is chosen for its relatively higher tensile strength and shear strength compared to concrete, making it a safer option when used as structural components in earthquake-prone areas, particularly for residential buildings. This situation must be anticipated by seeking alternatives to the use of natural forest wood with other wood-based materials that have significant potential, can be well-utilized, and can replace natural forest wood as a construction material and for other human needs. For example, the use of composite products like laminated wood made from fast-growing wood species can be an alternative. This can be sourced from cultivated trees in Community Forests or Industrial Timber Plantations. This research focuses on examining the potential use of fast-growing wood as structural elements by evaluating the physical properties of both solid wood and laminated wood. The main objective of this research is to address the scarcity of wood or wood resources from natural forests. The method used in this study involves selecting three types of fast-growing wood, followed by physical property testing in a laboratory.